2019
DOI: 10.3389/fgene.2019.00445
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and Population Genetics of Vicugna vicugna: Evolution in the Arid Andean High Plateau

Abstract: The vicuña ( Vicugna vicugna ) is the most representative wild ungulate of the high Andes of South America with two recognized morphological subspecies, V. v. mensalis in the north and V. v. vicugna in the south of its distribution. Current vicuña population size (460,000–520,000 animals) is the result of population recovery programs established in response to 500 years of overexploitation. Despite the vicuña’s ecosystemic, economic and socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…Similarly, the genetic diversity measured in terms of haplotype sharing between ancient and modern samples, or the number of haplotypes and total number of substitutions observed in both datasets ( Figure 7 ), also shows that the ancient samples presented significantly more genetic variation than the modern ones, with the vicuña having lost the most genetic variation across time. The latter is consistent with the evidence for bottlenecks in the species ( Wheeler, 1995 ; Casey et al, 2018 ; González et al, 2019 ; Fan et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, the genetic diversity measured in terms of haplotype sharing between ancient and modern samples, or the number of haplotypes and total number of substitutions observed in both datasets ( Figure 7 ), also shows that the ancient samples presented significantly more genetic variation than the modern ones, with the vicuña having lost the most genetic variation across time. The latter is consistent with the evidence for bottlenecks in the species ( Wheeler, 1995 ; Casey et al, 2018 ; González et al, 2019 ; Fan et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…To elucidate the origin and evolutionary history of camelids, numerous studies have performed DNA analyses on extant specimens (e.g. Fan et al, 2020 ; González et al, 2019 ; Marin et al, 2013 ; Marín et al, 2017 ; Casey et al, 2018 ; Marín et al, 2007a ; Wheeler et al, 2006 ; Kadwell et al, 2001 ; Stanley et al, 1994 ). However, the conclusions drawn from these studies are ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…The current study identified a total of 82 haplotypes in dromedary camels. This is relatively high when compared to Bactrians, llamas, and vicuñas, which only had 15, 17, and 57 haplotypes, respectively (Ming et al, 2017;Casey et al, 2018;González et al, 2019). However, these numbers might be correlated with the overall population size of the different camelid species, since dromedaries have a much higher population size than these other species (FAO, 2013(FAO, , 2017.…”
Section: Overall Genetic Diversitymentioning
confidence: 99%
“…Together with other camelids, alpacas are also of particular biological, biomedical and evolutionary interest due to their adaptations to extreme environments [10,11], unique and unusual features of their adaptive immune system [12][13][14][15] and as a basal clade of Cetartiodactyla in the mammalian phylogenetic tree [16,17]. Furthermore, the evolutionary history, genetic relationships and population structure of the alpaca and other South American camelids (llama, Lama glama; guanaco, Lama guanicoe and vicuña, Vicugna vicugna), continue to be topics of interest and debate [18][19][20].…”
Section: Introductionmentioning
confidence: 99%